A Study on improving the durability of drone according to the area of impact applied with finite element analysis method - Kwang Choi, Kye; Ung Cho, Jae (International Journal of Engineering and Technology, 2018)
The objective of this paper is to identify the dangers of damage on drones according to the area of impact and obtain the basic data for improving the durability. The durability by impact according to the weight and speed of the large-size drone is calculated and analyzed using a finite element analysis method with 3D model according to the area of impact. For the analytical results, the possibility of fracture is identified and weak areas are improved through the distribution of equivalent stress and deformation analysis using polyester resin, which is a material used for the drone. The equivalent stresses applied to drones in head-on impact and broadside impact were 296.22MPa and 349.36MPa respectively. The broadside impact producing the highest fracture stress of over 300MPa and the bottom part of the battery pack is limited to a fairly narrow area, so the improvements can be made by reinforcing this area. The great damage may occur from rear impact as the results show 828.28MPa, which is much higher than the fracture stress at rear impact to be the greatest drawback. Also for the deformation results, the values of head-on impact and broadside impact were in the safety range according to the elongation rate, while the drone greatly suffered from deformation and damage in rear impact. At the simulation analysis, the change of material must also be considered along with the change in design for rear collision. It is thought to obtain the basic data for future designing of large-sized drones by referring the results of this research, and it may contribute to the improvement of drone durability. By applying this study result to the drone, it is thought to contribute to the improvement on the durability of drone design due to the area of impact.Â Â